Torcicolo Muscular Congénito - Bastos, Sara; Interna de Formação Específica em Medicina Física e de Reabilitação do Centro Hospitalar e Universitário de Coimbra, EPE. Coimbra, Portugal (2014)
Objective: To describe the clinical patterns and characteristics of congenital muscular torticollis.Methods: Retrospective longitudinal study of the children with congenital muscular torticollis followed in Paediatric Rehabilitation consultation of the Centro Hospitalar e Universitário de Coimbra, between January 2008 and November 2011.Results: From a total of 91 CMT infants, 67% were boys and the mean age was 20 weeks. Difficult labour history was present in 72.9% cases, 61.1% from primiparous mothers and 14 had an abnormal delivery presentation. Cervical palpation revealed a tumour in 43.8% cases and there was a limitation in range of motion of the neck in 63.8%. All children have had home program executed by caregivers and 78 were following a rehabilitation program. Most children showed a complete regression of the condition and only one needed corrective surgery.Conclusions: Congenital muscular torticollis is the most common cause of wryneck in children. An early intervention is surely the key for a good outcome. Conservative treatment may attain good results in most cases.